2004
DOI: 10.1248/jhs.50.120
|View full text |Cite
|
Sign up to set email alerts
|

Current Hair Mercury Levels in Japanese for Estimation of Methylmercury Exposure

Abstract: Methylmercury (MeHg) is formed by saprophyte microorganisms from inorganic mercury compounds in the aquatic environment.1) It is accumulated in fish and shellfish through the marine food web. Since the MeHg accumulation increases with the food web, carnivorous fish such as tuna, swordfish and shark often exhibit high levels of mercury. Furthermore, due to the long biological half-life of MeHg, the chemical tends to accumulate throughout the life of fish.2) Marine mammals such as whales and dolphins also show h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…The influence of the fish consumption and the dietary habits on the THg concentrations in hair has been observed in the Rm Valcea (Fig. 3) as in several countries all over the world such as Cambodia (Agusa et al 2005), Bangladesh (Holsbeek et al 1996), USA (Knobeloch et al 2005), Amazonian areas (Dorea et al 2006), Japan (Akira et al 2004), Sweden (Johnsson et al 2004), Malaysia (Hajeb et al 2009), and Italy (Diez et al 2008;Gibicar et al 2009). …”
Section: Human Exposurementioning
confidence: 89%
“…The influence of the fish consumption and the dietary habits on the THg concentrations in hair has been observed in the Rm Valcea (Fig. 3) as in several countries all over the world such as Cambodia (Agusa et al 2005), Bangladesh (Holsbeek et al 1996), USA (Knobeloch et al 2005), Amazonian areas (Dorea et al 2006), Japan (Akira et al 2004), Sweden (Johnsson et al 2004), Malaysia (Hajeb et al 2009), and Italy (Diez et al 2008;Gibicar et al 2009). …”
Section: Human Exposurementioning
confidence: 89%
“…Lee et al (2000) observed that T-Hg and Me-Hg levels tended to increase with the age of subjects in males (P \ 0.01) for the urban residents of South Korea, but not in females. Yasutake et al (2004) observed a transient decline around the age of 20s, Hg levels increased into their 50s and 60s, and declined thereafter for the Japanese population. Hormonal control might be involved in Hg uptake by human hair for the Japanese.…”
Section: Age-related Variation In Hair Hg Levelsmentioning
confidence: 93%
“…The GM of Hg concentration was 0.81 µg/g [ 56 ]. Studies conducted in several different countries confirmed that hair Hg concentrations were affected by fish and shellfish intake [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. A study of women of childbearing age between 18 and 45 years reported a median of 0.32 µg/g and a linear tendency of Hg concentration increasing with the frequency of fish being eaten in a meal for a period of three months.…”
Section: Discussionmentioning
confidence: 99%